Switched - Calonita, Jen (Calonita, Jen. Fairy Tale Reform School., 2018)
Gilly and her friends must prepare for a giant invasion after Jack plants magic beans, earning him a spot in Fairy Tale Reform School and reminding Gilly how good it feels to be bad.